Decentralization, Saturation and Atomization: the State of the Architectural Digital Ecosystem - Nicolás Valencia (ARQ)
The rise of architectural blogs in the Web 2.0 era fundamentally transformed the production and consumption of architectural content, decentralizing the field from its traditional authorial, geographic, and institutional voices. What began as a force for diversity now confronts the challenges of atomization and algorithmic dominance, reducing critical engagement. As digital media remain in flux, the question persists: can architecture reclaim meaningful dialogue in an era increasingly defined by fragmented and superficial content?